ROMAN BAKHTALOVSKY (1897 – 1985), A PRIEST OF THE UNDERGROUND GREEK-CATHOLIC CHURCH: EVERYDAY LIFE THROUGH THE PRISM OF A CRIMINAL CASE - RAIKIVSKYI , Igor; YEHRECHII, Oleg (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose is to do the research on the possibilities of revealing the everyday life of a priest Roman Bakhtalovsky by studying the criminal case against him on September 13, 1949, by the Soviet law enforcement agencies. The research methodology is based on the principles of historicism, systematicity, scientificity, objectivity, and the application of source research methods, in particular the method of internal criticism of sources. Scientific Novelty. Criminal cases as a type of primary sources, despite their peculiarities (a strong subjectivity, individual inaccuracies, a low level of representativeness, certain arbitrariness of interpretation), contain a significant resource of factual data, thereby supplementing the source base on the history of everyday life. Conclusions. The testimonies of the defendants (in particular, Father Roman Bakhtalovsky), due to their “subjectivity,” require a careful comparison with other primary sources, including memoirs, eyewitness accounts of the events, periodicals of that historical era, memoranda, and diaries. At the same time, they contain facts that reflect the everyday life of not only R. Bakhtalovsky himself, but also of many clergymen of the period of the “catacomb” Greek-Catholic Church, shedding light on their biography, appearance, material security, ideological beliefs, communicative environment, mentality, etc. The investigation materials reflect the subjective nature of these interrogations, bias in the selection of witnesses, facts of a psychological pressure on clergy and lay people. The criminal case as a source contains facts of R. Bakhtalovsky's detention, the circumstances of his arrest by the Soviet special agencies, interrogations, examinations of his handwriting, decisions on bringing charges, a sentence, etc. Key words: criminal case, Father Roman Bakhtalovsky, underground Greek-Catholic Church, historical monument, everyday life, Soviet special agencies.